“I am Head and Gouernour of all the People in my Dominion”: An Analysis of the Speech Delivered by King James I in the London Parliament in 1604 - Radó, Bálint (FOCUS: Papers in English Literary and Cultural Studies, 2004)
Whig historiography has always maintained that King James I (1603-1625) was a theoretician of absolutism. It is for this reason that Whig “hagiography” has underlined that the MPs were eager to thwart the ruler’s absolutist policy. My chief aim in this article is to prove that in his speech in 1604 the Sovereign did not express any absolutist ideas. In order to be an absolutist political thinker one has to claim that neither the Parliament nor any other organ can have a share in legislation. “Princeps legibus (ab)solutus est” is how the Roman lawyer Ulpian formed this principle in the Antiquities. The ruler is not bound by human laws; he stands above them; he is the only source of laws in his realm. The Trew Law o f Free Monarchies written by James when he was King “only” in Scotland, (i. e. King James VI) provides a good ground for comparison. Thereby the obvious differences between the two aforementioned works of the ruler will be made clear.